Peningkatan Pendapatan Keluarga Melalui Diversifikasi Olahan Pisang di Masa Pandemi Covid 19 - supriyanti, yuni indah (JURNAL ABDIMAS SERAWAI, 2021)
ABSTRACT Partners in community service activities are PKK RT 2 (partner 1) and PKK RT 5 (Partner2) Kelurahan Kemumu. Base of  discussion result with partners founded: The first problem,   understanding of banana processing diversification was still low. The second problem, partners was unable to processed banana products into varied, unique, interesting and innovative products. The third problem,  the packing skills of partner products was still low. The solution that is planned is 1. Food Diversification counseling  2. Workshope make banana flour and a banana cake. 3. To create attractive and innovative products, a product packing system is also very necessary,  product packing system workshop is planned. The first objective of the Community Service activity is to improve the skills of banana processing diversification,  with a target that 80% of participants  have the skills to process the banana into flour properly. The second goal, partners can make varied, unique, interesting and innovative food from semi-finished ingredients (banana flour). The second activity target is as many as 85% have good skills in processing bananas that are varied, unique, interesting and innovative. The third activity target is 85% of partners have good packing system skills so that the product has a high selling value. The three goals have an outcome in increasing family income. The method of implementation uses a small group and  method workshop by applying a health protocol. As a result of the community service activities, there is an increase in knowledge of the diversification of processed bananas, including banana flour and banana cake. In addition, there is also an increase in skills in packaging systems and an increase in the selling value of processed bananas. The increase in the selling value of processed bananas has an impact on increasing family income. KEYWORDS: Food Diversification, Increasing family income